Simulation of carbon pricing and tax impact on corporate profitability using an econometric model - Wailan’An, Evi Juita; Pandia, Sonya Enda Natasha S; Hidayat, Akmal (Edelweiss Applied Science and Technology, 2025)
This study analyzes the simulated effects of carbon pricing and corporate tax rates on company profitability in five BRICS countries using panel data from 2022–2024. A fixed-effect panel regression model is employed with GDP growth as a control variable. Results show that both carbon pricing and corporate tax rates significantly reduce profitability, with coefficients of -0.21 to -0.29 and -0.11 to -0.16, respectively (p < 0.01). In contrast, GDP growth is positively linked to profitability. Simulations suggest that a 0.05 increase in carbon pricing may reduce ROA by up to 1.35 points in Brazil, while a similar rise in tax rates lowers ROA by about 0.55 points in India. These findings highlight the cost burdens of environmental and fiscal policies, stressing the need for balanced approaches that align emission reduction with business sustainability. This study contributes by providing country-level quantitative simulations through econometric panel methods, offering insights into the economic risks of carbon pricing and taxation in BRICS.